JUDGMENT CONSIDERATIONS ON THE DECISION AGAINST THE INDICT ABUSES OF NARCOTIC DRUGS WHICH HAVE BEEN RUNNING REHABILITATION IN THE STAGE OF THE INVESTIGATION - Ilham Gunawan Putra; Fitriati . (UNES Journal of Swara Justisia, 2020)
Rehabilitation for narcotics abusers is regulated in Article 54 of the Republic of Indonesia Law No. 35/2009 concerning Narcotics. This research is a legal research with Normative Juridical approach. With respect to the defendant being rehabilitated at the investigation stage, the Judge considered cutting off the rehabilitation period that had been carried out. Whereas in another decision at the investigation stage the defendant had undergone medical rehabilitation. In consideration of Decision Number 7 / Pid.Sus / 2018 / PN / Pmn it can be seen that the Judge did not consider the rehabilitation period that had been served by the defendant. It is different from Decision Number 24 / Pid.Sus / 2016 / PN / Pmn which considers the rehabilitation period that has been lived by the defendant. In the decision No. 7 / Pid.Sus / 2018 / PN / Pmn the defendant is no longer subject to the rehabilitation period only having to undergo a prison sentence imposed by the Judge on him.